2016
DOI: 10.1103/physrevd.93.104009
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Josephson junction from massive gravity

Abstract: We study the holographic superconductor-normal metal-superconductor (SNS) Josephson junction in de Rham-Gabadadze-Tolley massive gravity. If the boundary theory is independent of spatial directions, i.e., if the chemical potential is homogeneous in spatial directions, we find that the graviton mass parameter will make it more difficult for the normal metal-superconductor phase transition to take place. In the holographic model of the Josephson junction, it is found that the maximal tunneling current will decre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Furthermore, it was shown that the mentioned massive gravity has sensible effects in metal/superconductor phase transition. It was pointed out that for this phase transition, the maximal tunnelling current and the coherence length of junction are affected by the mass of graviton in Vegh's massive gravity model [67]. In addition, phase transition of holographic entanglement entropy in this massive gravity is investigated as well [68].…”
Section: Jhep05(2016)029mentioning
confidence: 99%
“…Furthermore, it was shown that the mentioned massive gravity has sensible effects in metal/superconductor phase transition. It was pointed out that for this phase transition, the maximal tunnelling current and the coherence length of junction are affected by the mass of graviton in Vegh's massive gravity model [67]. In addition, phase transition of holographic entanglement entropy in this massive gravity is investigated as well [68].…”
Section: Jhep05(2016)029mentioning
confidence: 99%
“…The properties of massive solutions have been studied in different scenarios [9]. From holographic point of view, the behaviors of different holographic quantities have been studied [5,[10][11][12][13][14][15][16][17][18][19][20][21][22]. The behavior of holographic conductivity for systems dual to linearly charged massive black branes has been explored in [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [11], a holographic superconductor has been constructed in the massive gravity background. [13] studies holographic superconductor-normal metal-superconductor Josephon junction in the massive gravity. Also the holographic thermalization process has been investigated in this context [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we will fix the parameters c 0 = c 1 = 1, c 2 = −1/2 in order to render the background thermodynamically stable [35,39]. The temperature of the black hole is readily obtained as…”
Section: Jhep07(2017)082mentioning
confidence: 99%
“…Therefore, from this aspect the graviton mass plays the role of inhomogeneity in the boundary field theory, i.e., greater graviton mass is dual to greater inhomogeneity in the boundary. 1 There have been a number of papers investigating the inhomogeneous effects caused by massive gravity so far, see for example [35][36][37][38][39][40][41][42][43].…”
Section: Jhep07(2017)082mentioning
confidence: 99%